Shaping the female student: an analysis of Swedish beauty school recruitment texts. Issue 2 (3rd May 2016) - Bredlöv, Eleonor
ABSTRACT: This study focuses on the recruitment of adults to the beauty industry in Sweden. It is concerned with a move in (beauty) education away from state and towards private provision in a wider context where education is becoming more heavily marketised. Drawing on a poststructural approach inspired by the work of Foucault and feminist theory, the shaping of student subjectivity in recruitment material for private beauty schools is analysed. A poststructural approach provides analytical tools that make visible the process of how power shapes subjectivities, and the use of feminist theory gives special focus to the gendered aspects of this process. The study includes a textual analysis of website homepages of beauty schools, beauty schools' Facebook pages and web pages that provide compiled information on educational programs and courses connected to the beauty industry. The analysis shows how consumption is constituted and feminised through specific marketing strategies and thereby becomes both a starting point and a resource for the shaping of student subjectivity. Thus, a particular form of gendered entrepreneurial self is shaped in this femininised educational context, and this study therefore highlights the importance of vocational research that takes into account the shaping of student subjectivity.